FRI0315 Congenital heart block in a cohort of pregnant women with anti-ro/ssa and/or anti-la/ssb antibodies. (23rd January 2014) - Palasti, S. M.; Dominguez, V.; Masoller, N.; Ramirez, J. C.; Teixido, I.; Cervera, R.; Figueras, F.; Espinosa, G.
Abstract : Background: Maternal autoimmune-mediated fetal heart disorders include a wide spectrum of conduction disturbances that can appear in fetuses of pregnant women with systemic autoimmune diseases, being congenital heart block (CHB) one of the most common and severe manifestations. The pathogenic role of maternal anti-Ro/SSA and anti-La/SSB antibodies has been well established in several studies. Objectives: To describe the characteristics of maternal autoimmune-mediated fetal heart disorders in a cohort of pregnant women with anti-Ro/SSA and/or anti-La/SSB antibodies from an Autoimmune Diseases Pregnancy Clinic of a tertiary hospital. Methods: We conducted a retrospective study to describe the prevalence of maternal anti-Ro/SSA and anti-La/SSB antibodies and their relationship with fetal heart disorders in pregnant women referred to our Autoimmune Diseases Pregnancy Clinic from1 st January 2009 to 31 st of December 2012. Results: A total of 133 pregnant women were referred to our clinic. The mean (SD) age was 35 (5.2) years and 123 (94%) were Caucasian. 63 (49%) women had SLE, 26 (20%) primary antiphospholipid syndrome, 11 (8%) primary Sjögren Syndrome (SS), 30 (22%) had other systemic autoimmune diseases and 3 (1%) were asymptomatic carriers of autoantibodies. Anti-Ro/SSA and/or anti-La/SSB antibodies were detected in 48 (36%) of these pregnant women: 47 (35%) had anti-Ro/SSA and 29 (22%) anti-La/SSB antibodies (both autoantibodies were detected in 26 (20%) women). CHB was detected by fetal echocardiography in 5 fetuses: Complete CHB (third degree) in three fetuses and second-degree CHB in the other two. The mean (SD) gestational age at the time of CHB detection was 21.8 (2.1) weeks. Four women were positive for anti-Ro/SSA and anti-La/SSB antibodies and the remaining was positive for anti-Ro/SSA. Three mothers were asymptomatic carriers of these antibodies and two had primary SS. Two women presented CHB in previous pregnancies; one was an asymptomatic carrier of anti-Ro/SSA and anti-La/SSB antibodies and the other had primary SS, respectively. Regarding fetal outcomes, the two women with second-degree CHB received dexamethasone and the newborns did not require any intervention. Among newborns with complete CHB, one needed a perinatal pacemaker implantation; one suffered an intrauterine fetal death and in the remaining the pregnancy was interrupted after the diagnosis of hydrops. Conclusions: All mothers of the fetuses with CHB from our cohort presented anti-Ro/SSA antibodies. They represented 10.6 % of the pregnant women with anti-Ro/SSA antibodies. Fetal echocardiography allowed the prenatal diagnosis and guided the management of the disease. Early serological and ultrasound screening is strongly recommended to recognize CHB in pregnant women with these antibodies. Disclosure of Interest : None Declared